Student hub: under the Lepidoptera / Nur Zarisha Abdul Halim, Nurul Fatihah Mohd Lazim and Nurrajwani Abdul Halim - Abdul Halim, Nur Zarisha; Mohd Lazim, Nurul Fatihah; Abdul Halim, Nurrajwani (2024)
A pavilion can be a temporary structure, built for leisure or shelter. It can also be an annex or add-on to a larger building, or it can be one of a group of buildings all standing together. Pavilions are flexible, open architectural structures, usually erected in parks and gardens. A pavilion provides a comfortable area shielded from both the sun and rain where tables, chairs, and other outdoor furniture or furnishings can be set up for hosting and/or relaxation. They played a significant role in political and cultural propaganda through international exhibitions in the 19th century, as well as in the presentation of new technologies and materials.